Case Report: Multimodal Imaging of Toxic Retinopathies Related to Human Immunodeficiency Virus Antiretroviral Therapies: Maculopathy vs. Peripheral Retinopathy. Report of Two Cases and Review of the Literature - Hammer, Arthur; Borruat, François-Xavier (Frontiers in Neurology, 2021)
Purpose: We report two patients with toxic retinopathy from either ritonavir or didanosine and reviewed the literature on the topics. We provide an overview of the retinal toxicity of these two antiretroviral drugs in human immunodeficiency virus-positive patients. Methods: First, we performed a retrospective study of the medical charts of two patients examined by us, one with ritonavir maculopathy and one with didanosine peripheral retinopathy. Secondly, we searched the world literature for similar cases through PubMed and Google Scholar, using the terms “HIV,” “AIDS,” “ritonavir,” “didanosine,” “maculopathy,” “retinopathy,” “visual loss,” and “toxicity” to retrieve the appropriate literature on the subject. Results: Patient 1: A 49-year-old woman complained of progressive central visual loss over the past 12 months. History disclosed ongoing ritonavir therapy for the past 11 years. Ritonavir maculopathy was diagnosed, and visual loss increased relentlessly despite cessation of treatment. Patient 2: A 55-year-old man complained of slowly progressive peripheral visual field constriction for the past 5 years. History disclosed didanosine therapy for 13 years, however, stopped 4 years before the onset of visual symptoms. No alteration of therapy was offered to patient 2 as didanosine therapy was interrupted 9 years previously. Since 2011, 11 cases of ritonavir maculopathy have been reported in the literature. Relentless worsening of vision was reported in 3/7 patients despite cessation of ritonavir therapy. Didonasine peripheral retinopathy was first described in 1992, and a total of 24 patients have been reported since. Relentlessly progressive peripheral retinopathy was diagnosed despite the previous cessation of therapy in 14 patients. Conclusion: Ritonavir causes a slowly progressive atrophic maculopathy, and didanosine toxicity results in a relentlessly progressing peripheral atrophic retinopathy. The relentless progression of both toxic retinopathies reflects permanent alterations of the retinal metabolism by these medications. Both ritonavir and didanosine toxic retinopathies are rare events, but their clinical presentation is highly specific.